Teacher characteristics: What do efl pre service teachers expect? - Dinh, Thu Hien (H. : ĐHQGHN, 2020)
Desirable characteristics of TEFL (Teacher of English as a Foreign Language) have recently presented a major concern for researchers, particularly in the realm of teacher education. However, no matter how large the number of research projects conducted in the field is, very few ever investigated the perspective of pre-service teachers. This mixed-method research was then conducted to identify characteristics of a good TEFL, as perceived by pre-service teachers. Participants were 117 students at Faculty of English Language Teacher Education (FELTE), University of Languages and International Studies (ULIS), Vietnam National University Hanoi (VNU), who were being trained to be English teachers. Self-report questionnaire and semi-structured interviews were employed to collect quantitative and qualitative data respectively. As indicated by the results, remarkable pedagogical skills and excellent content knowledge are highly expected for TEFL. Further qualitative analysis shows that this ideal image stems from pre-service teachers’ conception of TEFL’ roles as transmitters of knowledge, and that teaching is considered a profession with certain sets of expertise required. Overall, the research has demonstrated FELTE pre-service teachers’ expectations of teacher qualities, which to some extent, also revealed their didactic beliefs. These findings are hoped to offer implications for both student teachers and trainers working in EFL teacher education.